TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN KLINIK KECANTIKAN "WSJ" DI DEPOK BERDASARKAN PERATURAN PERLINDUNGAN KONSUMEN DI BIDANG KESEHATAN: Responsibility of Business Operators Towards Consumers of The "WSJ" Beauty Clinic in Depok Based on Consumer Protection Regulations in The Field of Health - Faza Shaumy Afiifah; Sharda Abrianti (Reformasi Hukum Trisakti, 2026)
This article highlights the responsibility of business actors in providing safe, high-quality, and transparent services in accordance with Law No. 8 of 1999 concerning Consumer Protection and Law No. 17 of 2023 concerning Health related to cases of malpractice in liposuction procedures at the “WSJ” Clinic in Depok. The research method used is normative research with a legislative approach supported by secondary data and qualitative analysis. The results of the study show that the business actor was proven to be negligent because they provided invasive health services that were not in accordance with the primary clinic's operating license and violated various provisions of laws and regulations, including Minister of Health Regulation No. 9 of 2014 and Law No. 17 of 2023 concerning Health. These violations included the use of medical personnel without a license to practice and the performance of high-risk medical procedures without adequate operational standards. Although legally liable for administrative, criminal, and civil liability, in practice, business operators were only subject to administrative sanctions in the form of revocation of their operating license and the obligation to compensate the victims' families.